Accuracy of estimating left ventricular ejection fraction in clinical routine. A SWEDEHEART registry validation study. (14th October 2021) - Lenell, J; Lindahl, B; Karlsson, P; Batra, G; Erlinge, D; Jernberg, T; Spaak, J; Baron, T
Abstract: Objective: Patients admitted to Swedish hospitals with myocardial infarction (MI) are reported to the nationwide Swedish registry for MI (SWEDEHEART). During hospital stay an echocardiography is routinely performed, and left ventricular ejection fraction (LVEF) is assessed according to the clinical praxis. LVEF is categorized as normal (>50%) or mild, moderate or severely impaired (40–49%, 30–39% and <30%, respectively) and reported to the registry by the treating center. The purpose of this study was to validate the reported LVEF assessments against independent echocardiography re-evaluation as this has never previously been done. Methods: A random sample of 130 patient from three different hospitals were included. LVEF re-evaluation was performed by two independent reviewers using the modified biplane Simpson method and their mean LVEF was compared to the SWEDEHEART LVEF. Agreement between reported and re-evaluated LVEF was assessed using Gwet's AC2 statistics. Results: Analysis showed good agreement between reported and reevaluated LVEF (AC2: 0.76 [95% CI 0.69–0.84]). The LVEF re-evaluations corresponded with registry reported categorized LVEF in 66.0% of cases. In 25.4% of cases the SWEDEHEART LVEF was lower than re-evaluated LVEF. The opposite relation was found in 8.6% of cases (p<0.005). Conclusion: Independent validation of SWEDEHEART-reported LVEF shows an overall good agreement with the re-evaluated LVEF. However, a tendency to underestimation of LVEF was observed in patients with impaired LV systolic function, in whom the reported assessment of LVEF should be interpreted more cautiously. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Selanders Stiftelse